Direct Repair of the Superior Band of Bigelow's Ligament after Hip Arthroplasty: A Surgical Technique. Issue 2 (July 2016) - Liu, Joseph; McLawhorn, Alexander S.; Christ, Alexander B.; Dzenis, Peteris; Healey, John H.
Background: The posterolateral approach is one of the most common approaches used during hip arthroplasty. A posterior soft tissue repair is necessary to limit the risk of postoperative dislocation. For a trapezoidal capsulotomy, the proximal limb divides the superior band of the iliofemoral ligament (Bigelow's ligament). A transosseous repair frequently leaves a defect in this region, which may elevate the risk for dislocation. The purpose of this article is to describe a simple, rational technique for reinforcing the posterior capsular repair. Description of Technique: A meticulous exposure of the hip capsule is performed during the posterolateral surgical approach. A trapezoidal capsulotomy is performed. After implantation of the arthroplasty implants, retractors are placed to expose the superior capsule. Prior to transosseous repair of the capsule and short external rotator tendons, the proximal limb of the capsulotomy is reapproximated anatomically and repaired with non-absorbable sutures. If anatomical repair is not possible, leg length and femoral offset should be reassessed carefully. Discussion: The described modification may further minimize the risk of dislocation following hip arthroplasty, as the superior band of Bigelow's ligament is an additional checkrein to internal and external rotation. This repair provides a secondary intraoperative assessment of leg length and femoral offset to ensure proper biomechanical reconstruction of the hip joint. It is the authors' preferred technique of all hip hemiarthroplasties and total hip arthroplasties, whenever possible.